Pengaruh mekanisme good corporate governance dan financial distress terhadap earning management (Studi empiris pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia) - Dewi Arum Sari; Edyanus Herman Halim; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of corporate governance mechanisms and financial distress on earnings management in manufacturing companies listed in Indonesia Stock Exchange (BEI) in the year 2009-2011. Variables tested in this study consists of institutional ownership, managerial ownership, the proportion of independent board, audit committee, financial distress and earnings management.This study used purposive sampling technique, the sample of 119 companies selected from 131 companies. In this study using regression analysis and descriptive statistics for the analysis of the data with the help of the program eviews 6.0.The analysis shows that institutional ownership, managerial ownership, the proportion of independent board no significant positive effect on earnings management. While the audit committee and financial distress significant negative effect on earnings management.Keywords: Institutional Ownership, Managerial Ownership, Board proportion Independent Commissioner, Audit Committee, Financial Distress and Earnings Management.